Moisture enhancement of niosomes entrapped with mineral water in pig ear skin - Manosroi A. (2014)
The objective of this study was to investigate transdermal absorption through the pig ear skin of niosomes entrapped with mineral water for the evaluation of skin moisture enhancement effects. Niosomes composing of Span 20, 40 and 60 mixed with cholesterol at 1:1 molar ratio were prepared by the conventional chloroform film method with sonication. The entrapment efficiency of mineral water using Na+ as a marker in Span 40, 20 and 60 niosomes were determined by atomic absorption. Transdermal absorption of Na+ and deuterium water in the form of deuterium ion from niosomes through the pig ear skin was performed by vertical Franz diffusion cells with the receiver chamber containing distilled water at pH 7.0 and 37 ± 2 °C. At time intervals of 8 and 48 hours, the samples from the receiver chamber were withdrawn and determined for the Na+ and deuterium ion contents by ion chromatography and an infrared spectrophotometer respectively. All niosomes entrapped with the mineral water showed physical stability at 4 ± 2, 30 ± 2 and 45 ± 2 °C for 6 months. The entrapment efficiency of mineral water in Span 40, 20 and 60 niosomes were 24.9 ± 1.81, 5.66 ± 0.46 and 5.14 ± 0.42 %, respectively. The Span 40 niosomal formulation entrapped with mineral water enhanced the pig ear skin moisture by the occlusive effect in blocking the water permeation pathway and sustaining Na+ in the skin.